Avaliação multicritério de topologias de máquinas elétricas para tração veicular - Santos, Leticia Gonçalves Tobias dos (My University, 2025)
The growing demand for sustainable solutions has been driving the development of more efficient electric propulsion technologies. In this context, the electric traction machine constitutes a critical component in electric and hybrid vehicles, with its selection influenced by technical, economic, and environmental factors. Traditionally, permanent magnet synchronous machines (PMSM), with radial flux configuration, stand out for their high efficiency and power density, justifying their widespread adoption by automakers. However, the dependence on rare earth materials raises concerns regarding price volatility and supply security, encouraging the search for alternatives. This work proposes a multi-criteria approach for the comparative evaluation of electric machine topologies for vehicle traction, through the combined application of the Analytic Hierarchy Process (AHP) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The methodology involves the definition of seven evaluation criteria (efficiency, power density, field-weakening operation, power factor, manufacturing cost, among others), the assignment of importance weights, and the systematic ranking of alternatives. Five topologies were analyzed: induction motor (IM), permanent magnet synchronous motor with radial flux (PMSM), synchronous reluctance motor (SynRM), permanent magnet-assisted synchronous reluctance motor (PMa-SynRM), and permanent magnet synchronous motor with axial flux (AFPM). The results indicated a preference for the PMa-SynRM topology for light vehicles (57%), for the SynRM topology for heavy vehicles (61%), and for the AFPM topology for in-wheel applications (62%). The analysis highlights the competitive potential of alternatives less dependent on rare earth materials in specific scenarios, confirming the effectiveness of the AHP-TOPSIS approach as a tool for the informed selection of electric machine topologies in the context of electric mobility. [resumo fornecido pelo autor]
A crescente demanda por soluções sustentáveis vem impulsionando o desenvolvimento de tecnologias de propulsão elétrica mais eficientes. Nesse contexto, a máquina elétrica de tração constitui um elemento crítico em veículos elétricos e híbridos, sendo sua seleção influenciada por fatores técnicos, econômicos e ambientais. Tradicionalmente, as máquinas síncronas de ímãs permanentes (PMSM), de fluxo radial, destacam-se pela elevada eficiência e densidade de potência, justificando sua ampla adoção pelas montadoras. Entretanto, a dependência de materiais de terras raras suscita preocupações quanto à volatilidade de preços e à segurança no suprimento, estimulando a busca por alternativas. Este trabalho propõe uma abordagem multicritério para a avaliação comparativa de topologias de máquinas elétricas para tração veicular, mediante a aplicação combinada do Processo Analítico Hierárquico (AHP) e da Técnica para Ordem de Preferência por Similaridade à Solução Ideal (TOPSIS). A metodologia contempla a definição de sete critérios de avaliação (rendimento, densidade de potência, operação com enfraquecimento de campo, fator de potência, custo de fabricação e outros), a atribuição de pesos de importância e a classificação sistemática das alternativas. Foram analisadas cinco topologias: motor de indução (IM), motor síncrono de ímãs permanentes de fluxo radial (PMSM), motor síncrono de relutância (SynRM), motor síncrono de relutância assistido por ímãs permanentes (PMa-SynRM) e motor síncrono de ímãs permanentes de fluxo axial (AFPM). Os resultados indicaram preferência pela topologia PMa-SynRM para veículos leves (57%), pela topologia SynRM para veículos pesados (61%) e pela topologia AFPM para aplicações in-wheel (62%). A análise evidencia o potencial competitivo de alternativas menos dependentes de terras raras em cenários específicos, confirmando a eficácia da abordagem AHP-TOPSIS como instrumento para seleção fundamentada de topologias de máquinas elétricas no contexto da mobilidade elétrica. [resumo fornecido pelo autor]
Keywords: Máquinas elétricas; Motores elétricos; Propulsão elétrica; Processo decisório por critério múltiplo; Engenharia mecânica; Electric machines; Electric motors; Electric propulsion; Multiple criteria decision making; Mechanical engineering